GLOBAL EXISTENCE OF CRITICAL QUASI-GEOSTROPHIC EQUATION IN CRITICAL SPACE - BEN ABDALLAH SABER (University Of Eloued جامعة الوادي, 2020)
we show the global existence for quasi-geostrophic equations if ........ is small enough; among others we prove the analyticity of such a solution. If in addition the initial condition veri es ...... with ....., then the solution remains regular. Fourier analysis and standard techniques are used.
Intervention Abstract